Nurses' Roles in the Implementation of the Fourth Patient Safety Goals: Literature Review - Fairuza Fajar Yumna; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur; Retno Purwandari; Yulia Kurniawati (KHD Production, 2025)
Patient safety is a critical component of healthcare quality. Surgical procedures pose significant risks, with frequent incidents such as wrong-site surgeries and retained surgical instruments. To mitigate these risks, the Fourth Patient Safety Goals emphasize the correct site, correct procedure, and correct surgical patient. Nurses, who are involved in every stage of surgical care, play a vital role in ensuring of the correct site, procedure, and surgical patient. The objective of this research is to analyze and identify the role of nurses in implementing the Fourth Patient Safety Goal, specifically in ensuring the correct site, procedure, and patient in surgical settings. This study employed a literature review method using databases including Google Scholar, PubMed, and Science Direct. A total of 11 articles published between 2024 and 2025 were selected using inclusion and exclusion criteria based on the PICO(S) approach. Article quality was assessed using JBI Appraisal Tools. The findings show that nurses contribute significantly to all three phases of the Surgical Safety Checklist (sign in, time out, sign out). Their roles include verifying surgical information, ensuring team communication, providing emotional support for patients, coordinating interdisciplinary collaboration, and integrating technology-based tools. Barriers identified include lack of training, incomplete documentation, and limited compliance with protocols. Nurses play a central role in ensuring the correct site, procedure, and surgical patient. Strengthening their competence, fostering interprofessional collaboration, and applying technological innovations are essential strategies to enhance patient safety in surgical settings.